From Vision to Apocalypse: the Poetic Subject in Recent Mexican Poetry - Norma Klahn (Studies in 20th & 21st Century Literature, 1990)
Over the last two decades there have been significant changes in the poetic subject. After the colloquial realism of the fifties and sixties, in which the poetic subject acted as witness to his or her time or spoke as a collective subject, there has emerged, particularly in the poetry of José Emilio Pacheco, a poetry in which the subject assumes an impersonal voice. This poetry questions originality, privileging appropriation, parody and pastiche while becoming increasingly skeptical and apocalyptic.
Keywords: Mexican Literature; Mexican poetry; poetry; poetic subject; colloquial realism; José Emilio Pacheco; impersonal voice; voice; originality; appropriation; parody; pastiche; skepticism; apocalyptic